2018
DOI: 10.1016/j.omtn.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The Supercarbonate Apatite-MicroRNA Complex Inhibits Dextran Sodium Sulfate-Induced Colitis

Abstract: The incidence of inflammatory bowel disease (IBD) is increasing. Nucleic acid-based medicine has potential as a next-generation treatment, but it is rarely successful with IBD. The aim of this study was to establish a microRNA-based therapy in an IBD model. For this purpose, we used microRNA-29 (miR-29) and a supercarbonate apatite (sCA) nanoparticle as a drug delivery system. Injection of sCA-miR-29a-3p or sCA-miR-29b-3p into mouse tail veins markedly prevented and restored inflammation because of dextran sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…MiR-29b diminishes dendritic cells’ apoptosis and cytokine production 62 . However, its deletion exacerbates UC, while its overexpression helps managing the disease 63 . Whereas miR-29b is known to prevent inflammation 64 , it increases collagen production and fibrosis in IBD 65 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-29b diminishes dendritic cells’ apoptosis and cytokine production 62 . However, its deletion exacerbates UC, while its overexpression helps managing the disease 63 . Whereas miR-29b is known to prevent inflammation 64 , it increases collagen production and fibrosis in IBD 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the miR-29 family regulates myogenesis of muscle stem cells [16], chondrogenic differentiation of mesenchymal stem cells [17] and fibrosis matrix formation in inflamed tissue [18]. miR-29 signaling also modulates immune cell activation in multiple sclerosis [19], the host immune response [20] and inflammatory reaction in colitis [21]. We previously revealed that glucocorticoid induced bone loss and marrow adipose overdevelopment along with decreased miR-29a expression [22].…”
Section: Introductionmentioning
confidence: 99%
“… 21 In earlier studies, we had shown that sCA nanoparticles successfully delivered various nucleic acids or low molecular weight reagents in tumour or IBD (inflammatory bowel disease) model mice with no resulting apparent abnormalities in the body weight, blood chemistry tests or histology of normal organs of the mice. 18 22 , 53 56 Moreover, recent review articles have described various miRNA-based therapeutics, most of which employ local injection into tumours, and introduced sCA as a hopeful systemic strategy that could be delivered via intravenous administration. 50 , 57 Aiming towards clinical application, we have successfully developed an even less toxic and more efficient delivery system platform that is considered promising in terms of clinical potential.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted RNA sequencing as previously described. 18 The library was prepared using a TruSeq Stranded mRNA Sample Prep Kit (Illumina, San Diego, CA, USA). Sequencing was performed using the Illumina HiSeq 2500 platform in 75-base single-end mode.…”
Section: Methodsmentioning
confidence: 99%